2015
DOI: 10.1007/s11107-015-0531-1
|View full text |Cite
|
Sign up to set email alerts
|

A new proposal for eight-channel optical demultiplexer based on photonic crystal resonant cavities

Abstract: In this paper, we used the novel defective resonant cavities to design an eight-channel photonic crystal demultiplexer. We showed that by choosing appropriate values for the width of the resonant cavity, the desired wavelengths can be separated. The proposed platform has a square lattice of dielectric rods immersed in air. The value of transmission efficiency for channels was obtained in 94−99 % range. In addition, the maximum value of crosstalk and average quality factor for channels were calculated -11.2 dB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…In [15] everything looks well, but as we explained in the introduction, it cannot be fabricated because of the defect radii they chose. In [16] we can see better results than for the others. Comparing our study with [16], although the average passband of their structure is lower and as a result the quality factor of their proposed demultiplexer is higher, we improved the average channel spacing and also the crosstalk value.…”
Section: Simulation Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…In [15] everything looks well, but as we explained in the introduction, it cannot be fabricated because of the defect radii they chose. In [16] we can see better results than for the others. Comparing our study with [16], although the average passband of their structure is lower and as a result the quality factor of their proposed demultiplexer is higher, we improved the average channel spacing and also the crosstalk value.…”
Section: Simulation Resultsmentioning
confidence: 64%
“…They showed that by choosing appropriate values for the width of the resonant cavity, the desired wavelengths could be separated. The average channel spacing and quality factor they reported were close to 2.1 nm 2200, respectively [16].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The demultiplexing operation was done by choosing different values for the width of the cavities. The result was a structure with channel spacing and quality factor equal to 2.1 nm and 2200 respectively [39].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, two-dimensional (2D) and three-dimensional (3D) PCs are defined when the dielectric constant varies along two and three direction, respectively [1][2][3][4]. PBG property made these artificial structures suitable for designing different optical devices such as filters [5][6][7][8][9][10][11], demultiplexers [12][13][14][15][16][17] switches [18][19][20] and optical logics [18,[21][22][23][24][25][26][27][28]. The optical power splitter or divider is an indispensable component in photonic-integrated circuits which is used in fiber optic networks.…”
Section: Introductionmentioning
confidence: 99%